MANAJEMEN OPERASIONAL PENDIDIKAN MASA PANDEMI COVID 19 DI RA PERWANIDA WONOSOBO - Mardiyati, Laily; Imron, Imron (Prosiding University Research Colloquium, 2021)
The increasingly widespread spread of COVID-19 requires that learning in schools be carried out online. The problem that has arisen due to Covid-19 is the operational costs of schools, this also occurs at RA PERWANIDA WONONOSOBO, as a private educational institution. They rely on fees from their parents for school operational costs. When many parents stop working or their income drops, it is possible that they do not pay tuition fees to school. In a situation like this, schools don't get income so they can't afford teachers' salaries, this becomes a big problem. This research is a qualitative research. Collecting data using interview, observation and documentation methods. Test the validity of the data using triangulation techniques. Data analysis used a description technique with the Miles and Huberman interaction analysis model with the flow including data collection, data reduction, and data presentation. With that, the head of RA PERWANIDA WONOSOBO builds cooperation with several guardians of students to meet the salaries of teachers and employees, including collaborating with several guardians of students who will later use the sales proceeds for capital and part of the income for school operational costs, as well as cooperation with others, this is done to fulfillment of school operational costs.